FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN LABA (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI) (Students' Journal of Accounting and Banking, 2014)
The purpose of this study is to examine and analyze the effect of the Current Ratio, Debt Equity Ratio, Inventory Turn Over, Return On Equity effect on profit growth in the manufacturing companies listed on the Stock Exchange in 2010-2011. Population used is a manufacturing company that went public on the Stock Exchange in 2010-2011, the number of samples by using purposive sampling techniques were as many as 127 companies. Types of data used are secondary data, such as financial statement data ICMD 2010-2011. Tool using multiple regression analysis. The results showed that the return on equity effect on profit growth. This condition occurs because the ratio between net income compares with total assets. This ratio measures how much of the operating income earned from each dollar of assets owned by the company. Debt to Equity ratio effect on profit growth. This condition occurs because the ratio is the ratio of total liabilities (debt) to total capital owned. The higher capital used to finance the debt the more likely it is expected to generate a profit, because the company is considered to be able to resolve its debt with its equity. Current ratio is not significant effect on earnings growth. This condition occurs because the lower the ratio, the more it does not likuit company in running its operations, so that the profit down. Liquidity in this study was high, with an average of 227.47%, which means a lot of idle funds. Invetory turnover effect on profit growth. This condition occurs ratio is the ratio of the activity that is intended to measure up how much the effectiveness of the company in doing its resources, especially its capital. Keywords: Return On Equity, Debt Equity Ratio, Current Ratio, Inventory Turn Over, and Profit Growth